On the Structure and Significance of Augustine's Moral Grammar. Issue 4 (1st February 2022) - Westerholm, Martin
Abstract: This essay traces Augustine's understanding of the structuring elements that give shape to human becoming. It presents this understanding as a distinctive form of maximalism in thinking about happiness, justice, and power, and as standing apart from classical and modern alternatives in its approach to desire, power, and mediation. By tracing the way that Augustine develops a moral grammar across three distinctive constellations of concepts, it shows where influential interpretations of his work leave important elements behind, and wider contemporary conceptions may benefit from dialogue with his work.